A Novel Mitochondrial Targeted Compound Phosundoxin Showing Potent Antifungal Activity against Common Clinical Pathogenic Fungi - Shu Zhang; Yuanyuan Geng; Bin Wei; Yangzhen Lu; Lihua He; Fei Zhao; Jianzhong Zhang; Zhaohai Qin; Jie Gong (Journal of Fungi, 2023)
The current increase in resistance to antifungal drugs indicates that there is an urgent need to explore novel antifungal drugs with different mechanisms of action. Phosundoxin is a biphenyl aliphatic amide using a TPP-targeting strategy which targets mitochondria. To provide insights into the antifungal activities of phosundoxin, the antifungal susceptibility testing of phosundoxin was conducted on 158 pathogenic fungi and compared to that of traditional azole drugs. Phosundoxin displayed a broad-spectrum antifungal activity on all the tested yeast-like and filamentous fungi ranging from 2 to 16 mg/L. In particular, azole-resistant clinical isolates of Candida albicans were susceptible to phosundoxin with the same MICs as azole-susceptible C. albicans. Transcriptome analysis on azole-resistant C. albicans identified 554 DEGs after treatment with phosundoxin. By integrating GO and KEGG pathway enrichment analysis, the antifungal activity of phosundoxin was related to impairment of mitochondrial respiratory chain function. Acute oral and percutaneous toxicity of phosundoxin to rats showed that the compound phosundoxin were mild toxicity and LD50 was above 5000 mg/kg body weight in rats. This study demonstrated the potential of phosundoxin as an antifungal agent for the treatment of common fungal infection and contributed to providing insights into the mechanisms of action of phosundoxin against C. albicans.